A Conversation with Howard Hogan, Former Chief Demographer at the United States Census Bureau. Issue 3 (3rd July 2022) - Eltinge, John; Martinez, Wendy
Abstract : John Eltinge and Wendy Martinez had the pleasure of interviewing Howard Hogan, the former Chief Demographer of the United States Census Bureau in September 2019. Howard had a long and distinguished career at the Census Bureau, where he started working in 1979. Howard obtained his Ph.D. in Economics and Demography at Princeton University, and he later earned a Master's Degree in Public Affairs from The Woodrow Wilson School. As Chief Demographer, Howard served as a senior scientist and principal consultant on methodological problems, as well as on technical and statistical demography. Throughout his career, he contributed to several professional organizations including the American Statistical Association (ASA), the Washington Statistical Society, and the International Association of Survey Statisticians. He was awarded Fellow of the American Statistical Association in 2001 and received the Jeanne E. Griffith Mentoring Award in 2018.